Our experience diagnosing 225 patients with cervical glandular lesions: current technologies, lessons learned, and areas for improvement - Yan Qin; Junyi Deng; Yuexian Ling; Tao Chen; Hongyi Gao (BMC, 2024)
Abstract Objective To explore the relative sensitivity of different methods for detecting cervical glandular lesions. Methods A total of 225 patients with cervical glandular lesions diagnosed from January 2018 to February 2023 were retrieved from the pathology database of Guangdong Maternal and Child Health Hospital, and their clinicopathological features were reviewed. Results Four human papillomavirus (HPV) genotypes: HPV18, 16, 45, and 52, dominated all glandular lesions, and accounting for 74.10% of HPV-positive tumors. Furthermore, 36.89% of abnormal squamous cells were diagnosed as abnormal based on cytological examinations leading to the detection of cervical glandular lesions; only 16.89% were diagnosed based on the initial detection of abnormal glandular cytology. The most common abnormal cervical screening result was ASC-US on cytology (14.22%), followed by HSIL (11.56%). Only few number of patients were diagnosed with or suspected of having cervical adenopathy via a Pap test (18.22%). Nearly one-third of cervical glandular lesions cases were not detected on the Pap test; but were diagnosed upon cervical biopsy or based on the histological examination of ECC, LEEP, or CKC specimens. The LEEP or CKC biopsy specimens had negative margins in 49 cases (40.83%), while the margins were positive in the other 71 cases (59.17%). Five cases (10.20%) with negative margins still had residual lesions following total hysterectomy, and 19 (26.76%) with positive margins had no residual lesions after total hysterectomy. Conclusion The ability to detect cervical glandular lesions varies for routine HPV genotyping, Pap test, or biopsy/ECC, with different sensitivities and advantages and disadvantages for each method.